Evaluation of Attitude and Performance of Nurses Attending In-service Training courses Regarding the Use of Professional Ethics in Educational Healthcare Centers of Zanjan, Iran - Hossein Gangineia; Mohammadreza Heidari; Alireza Shoghli; Mansoor Mohajer (Zanjan University of Medical Sciences and Health Services, 2018)
Background and Objective: The healthcare system seeks responsible nurses, who are committed to professional ethics, which is a vital requirement in this area. Therefore, this study aimed to determine the role of in-service training courses in the attitude of nurses toward professional ethics and their performance in three educational healthcare centers of Zanjan, Iran. Materials and Methods: This descriptive and cross-sectional research was performed on 400 nurses in educational healthcare centers of Zanjan, including 362 female (90.5%) and 38 male (99.5%) individuals, who were selected via convenience sampling. Data collection was carried out using the standardized questionnaire of ethics in nursing profession by Eun-Ja Yeun (2004) in the spring of 2018. Reliability of the mentioned survey was estimated at the Cronbach's alpha of 0.76. Data analysis was performed in SPSS version 21 at two descriptive and inferential levels. Results: From 400 nurses assessed, 53.5% attended the educational courses on professional ethics. According to our findings, no significant difference was observed between the subjects who attended the courses and those who did not participate in the educational classes in terms of attitude toward professional ethics. Moreover, no significant association was found in the performance of participants who attended the mentioned classes before and after the intervention. Conclusion: According to the results of the study, participation in educational courses on professional ethics failed to make a significant difference in the attitude and performance of nurses. Therefore, more attention must be paid to the implementation of educations and place of work of nurses.